Development and Implementation of Generic Special Education Training Programs for Regular Educators - Cartwright, G. Phillip ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The School District of Philadelphia developed inservice and other training programs to help regular teachers, administrators, and other school staff; parents; and nonhandicapped students become aware of and sensitive to the educational needs and rights of handicapped children. Four elements were considered essential minimums to the overall task--participants needed to know why the staff development program was to be carried out; participants needed to know who were the eventual subjects or beneficiaries of the training; participants needed to know what kinds of supportive services were in place or planned to help cope with the handicapped children; and participants needed to know what specific training, services, consulting, etc. would be available to help teachers or schools cope with daily problems. Some of the constraints or problems with implementing quality programs were considered, including those of size of the task, finances, and time. The overall plan involved such activities as training of 280 building principals, individual school based planning, and evaluation. Content of generic inservice programs addressed topics including supportive programs and personnel, methods of individualizing instruction in regular classes, and legal considerations. (SBH)
ERIC Note: Paper presented at the Annual Topical Conference in Special Education: Generic Special Education (1st, Baton Rouge, LA, February 14-15, 1980).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Disabilities; Inservice Education; Parent Attitudes; Program Development; Program Implementation; Student Attitudes; Teacher Attitudes; Philadelphia School District PA; Reports, Descriptive; Speeches/Meeting Papers